Inovasi Dilingkungan Di Kementerian Sekretariat Negara RI Dilihat Dari Perspektif Knowledge Management - Herman Supriadi; Martani Huseini (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The focus of this research is to describe the development of innovations in the Ministry of State Secretariat (Kemensetneg) from the perspective of Knowledge Management including the factors that influence it. This study uses a post-positivism approach with qualitative data collection methods, which result show that the development of innovations in the Ministry of State Secretariat has been going well, judging from the context of Socializaton, Externalization, Combination, and Internalization (SECI). Factors influencing the development of innovation are the existence of strong and effective leadership, the availability of human resources as a lever of change, organizational culture and policies that support innovation, and the supply and use of Information and Communication Technology (ICT) as a driving factor. However, there are still inhibiting factors, namely the limited budget for the development of innovation itself and the many innovations created in the form of applications that have not been integrated in the framework of the ministry’s big data through the use of machine learning